PERSONAL QUALITIES OF A TEACHER, THEIR ROLE IN THE PROFESSIONAL ACTIVITIES AND PEDAGOGICAL TECHNIQUE AS AN INTEGRAL PART OF PEDAGOGICAL SKILL - Gafurova N. (Galaxy International Interdisciplinary Research Journal, 2022)
The personal and individual qualities of a teacher must simultaneously meet two levels of requirements for this profession. The requirements of the first level are imposed on the teacher in general as a carrier of the profession. They are irrelevant to social conditions, social formations, educational institution, academic subject. Any real teacher should meet these requirements.